NIKAIA'DAN YENİ YAZITLAR V - (:unkn) unknown (My University, 2015)
Makalede 2010-2014 yılları arasında Nikaia antikkentinin teritoryumunda bulunan 14 adet yeni mezaryazıtı tanıtılmaktadır. Nikaia antik kentinin doğu teritoryumundan ele geçen tüm yazıtlar Roma İmparatorluk Çağı'na tarihlendirilmektedir. Bu yazıtlar, bölgeninkültürel zenginliğini gösteren çok sayıda anthroponymos isimler içermektedir.

This article presents 15 new funerary inscriptions found within the territory of Nicaea, during the course of surveys conducted between 2010 and 2014. All of these inscriptions came from the area which in the Roman imperial period formed a part of the eastern territory of Nicaea. These new texts include numerous anthroponyms, which underlines the cultural richness of this region.
NEW INSCRIPTIONS FROM NICAEA (V)
Keywords: Arkeoloji